Peran Lembaga Keagamaan dalam Dinamika Sistem Hukum Pidana di Indonesia - Kalingga, Qori Rizqiah H; Purba, Dhea Aulia M; Pratama, Adi (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
Religious institutions play a crucial role in shaping Indonesia’s criminal law system. Religious norms, particularly Islamic law, not only serve as a source of moral values but also contribute to the formation of positive legal norms. This study aims to analyze the role of religious institutions in Indonesia’s criminal law system. It employs a juridical-normative method with a qualitative approach, focusing on the analysis of legal texts, religious documents, and relevant scholarly works. Data were collected through literature study, drawing on sacred texts, legislation, religious decrees, and academic journals. The data were analyzed qualitatively through data reduction, data presentation, and inductive conclusion drawing. The findings reveal that religious institutions influence the formation of criminal law principles, such as justice, proportionality, personal responsibility, and humane treatment. The Islamic criminal law system, consisting of hudud, qishas/diyat, ta'zir, and makhzurat categories, serves as a selective reference within the national legal system. This study concludes that Indonesia's criminal law system results from a complex adaptation of religious norms, modern law, and social needs. Future research is recommended to explore the role of religious institutions in contemporary criminal policy, such as cybercrime and protection of vulnerable groups, through empirical studies.